Instituições regionais de desenvolvimento: análise do período 2003 a 2016 - Lourenço, Gabriel Floriano (2022)
This investigation aimed to debate the regional development superintendencies of the Northeast and North and their alternations throughout history, since the creation, the crises in the military period, the extinction and its resurrection in 2007 with the creation of the National Development Policy. Regional (PNDR I). As an alternative for the development of the Northeast and North regions, there are the regional development plans, which, in their documents, allow a representation in the institutional environment as two macro-regions and changes growth projects that can help the development and development of these regions. It was used as a methodology to understand all the institutional theories and the cycle of public policy processes to contextualize the PNDR II revision scenario, in addition to analyzing the financial reality of each region to finance its current development and each of them as perspectives. of future. Finally, it is verified that the development projects that expand the development project that encompass are important for the development project that encompass as more peculiar to the development of each national region are important to be developed as development projects that encompass as peculiar to each national region. development of each region.